"Which coping strategies does the working environment offer you?" A field study of the distributed nature of stress and coping. Issue 1 (2nd January 2016) - Kirkegaard, Tanja; Brinkmann, Svend
Abstract : This study explores work stress as a cultural phenomenon, distributed socially and materially, by introducing the metaphor of a landscape of appraisal and coping. By using this landscape analogy, it is emphasized that concrete contexts invite employees to appraise the situations at work in a certain way and afford using certain coping strategies rather than others. This study uses data based on a field study in one department of a multinational company and demonstrates how definitions of stress, appraisals of the working environment and coping strategies vary across professional groups. Furthermore, the study indicates that these different appraisal and coping practices are deeply embedded in the concrete context in the sense that the different aspects of the working environment such as the physical surroundings, the work organization, the social interactions and cultural characteristics both separately and combined invite the employees to engage in distinct appraisals and coping practices and limit the use of others. By invoking the landscape metaphor, we aim to expand our understanding of stress as something more than a transaction between the individual and a specific stressful situation at work.